Engineering for Rural Development 2019
DOI: 10.22616/erdev2019.18.n327
|View full text |Cite
|
Sign up to set email alerts
|

Studying the electrical characteristics of grain under vibration action

Abstract: Studies of the instrument error depending on the compaction of the grain sample in the sensor with free backfilling, forced sealing with a piston and under vibrating showed that the highest reproducibility of the readings, and therefore the lowest instrument error is provided, when exposed to vibration. Granular bulk materials change the volume only to a limited extent, even under the influence of external forces. The vibration action significantly reduces these forces, allowing the grains to be stacked more t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The experimental results described in [12] have shown that the value of the dielectric permeability (DP) of the grain mass (GM) in the vibro-fluidized layer decreases, starting with some values of the vibration amplitude with the growth of the latter.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The experimental results described in [12] have shown that the value of the dielectric permeability (DP) of the grain mass (GM) in the vibro-fluidized layer decreases, starting with some values of the vibration amplitude with the growth of the latter.…”
Section: Methodsmentioning
confidence: 99%
“…The electrical characteristics of grains and seeds are studied by many authors [1][2][3][4][5][6][7][8][9][10][11][12]. The issues of the influence of the vibration frequency on the reach-hrough conductivity of the vibro-fluidized grain mass have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The basic error of the vibration flow moisture meter [8][9][10] obtained as a result of the calculation should not exceed the permissible value. Otherwise, the graduation of the moisture meter is repeated.…”
Section: Table 2 Scheme For Calculating Auxiliary Values Of the Regression Equationmentioning
confidence: 99%